2013
DOI: 10.1103/physrevb.87.014408
|View full text |Cite
|
Sign up to set email alerts
|

Mn2FeSbO6: A ferrimagnetic ilmenite and an antiferromagnetic perovskite

Abstract: Due of its polymorphism, Mn2FeSbO6 can be synthesized at high pressures and temperatures as a ferrimagnetic ilmenite or an antiferromagnetic perovskite. The structural phase transformation is discussed in detail, and magnetic structures are proposed for both phases. The high-pressure Mn2FeSbO6 polymorph is a rare example of A2B B O6 perovskite with solely Mn cations on the A-site. Fe and Sb cations are ordered on the B-sites. Theoretical calculations for the perovskite phase suggest a complex magnetic structur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 28 publications
1
13
1
Order By: Relevance
“…The A 2 BB′O 6 ‐type corundum derivatives can crystallize in the centrosymmetric ilmenite (IL, space group R ‐3), or in non‐centrosymmetric LiNbO 3 (LN, R 3 c ), or ordered ilmenite (OIL, R 3), or Ni 3 TeO 6 (NTO, R 3) structure, as shown in Figure S1 (Supporting Information). The stabilization of any one of these structures depends on the cation arrangement and their ordering/disordering degree, which are affected by the cationic size and charge differences, electron configuration, and synthesis conditions . The general structural features of A 2 BB′O 6 ‐type corundum derivatives with octahedral coordination of all metal sites favor the formation of practical magnetic and multiferroic/magnetoelectric materials by incorporation of magnetic transition metal ions.…”
mentioning
confidence: 99%
“…The A 2 BB′O 6 ‐type corundum derivatives can crystallize in the centrosymmetric ilmenite (IL, space group R ‐3), or in non‐centrosymmetric LiNbO 3 (LN, R 3 c ), or ordered ilmenite (OIL, R 3), or Ni 3 TeO 6 (NTO, R 3) structure, as shown in Figure S1 (Supporting Information). The stabilization of any one of these structures depends on the cation arrangement and their ordering/disordering degree, which are affected by the cationic size and charge differences, electron configuration, and synthesis conditions . The general structural features of A 2 BB′O 6 ‐type corundum derivatives with octahedral coordination of all metal sites favor the formation of practical magnetic and multiferroic/magnetoelectric materials by incorporation of magnetic transition metal ions.…”
mentioning
confidence: 99%
“…Cationic rearrangements below 300 °C have only been reported in nanocrystals, or when driven by applied external electrical potential as in battery materials, but not in bulk metal oxides by temperature alone. The corundum‐derived A 2 BB′O 6 family of compounds can incorporate transition metal ions at all of the cationic sites and adopt different cation order–disorder configurations, providing an ideal platform for materials engineering . Recently, the polar room‐temperature ( T C ≈337 K) ferrimagnet Mn 2 FeMoO 6 , hereafter called phase I, was prepared by quenching to room temperature from 1350 °C at a pressure of 8 GPa .…”
Section: Figurementioning
confidence: 99%
“…The corundum-derived A 2 BB'O 6 family of compounds can incorporate transition metal ions at all of the cationic sites and adopt different cation order-disorder configurations, providing an ideal platform for materials engineering. [5,8,9,[17][18][19][20][21][22] Recently, the polar roomtemperature (T C % 337 K) ferrimagnet Mn 2 FeMoO 6 , hereafter called phase I, was prepared by quenching to room temperature from 1350 8C at a pressure of 8 GPa. [21] Firstprinciples calculations indicated that the band gap, the magnetic and electronic properties, and the ground-state energy of Mn 2 FeMoO 6 are governed by the arrangement of cations in the unit cell, which suggested effective property control through cationic arrangement.…”
mentioning
confidence: 99%
“…Sample 2 contained a minute impurity phase of the binary oxide NiSb 2 O 6 , whereas sample 1 was found to be a pure, single phase spinel without impurity phases. One original motivation for this study was to prepare and study the Ni based synthetic analog of the natural mineral melanostibite, Mn 2 FeSbO 6 , which crystallizes in the structural type ilmenite [16]. However, the ilmenite Ni 2 FeSbO 6 did not form in this preparation method.…”
Section: Sample Preparationmentioning
confidence: 99%